Odontoma and Analysis of 57 different types - Baghaei-; Ebrahimizadeh M (Tehran University of Medical Sciences, 1999)
Odontoma is an odontogenic lesion with epithelial and mesenchymal origin and is composed"nof differentiated dental parts. Than because of abnormal organization of mature tissues. It seems that it is"na hamartoma rather than real tumor. Odontoma is seen in two types of compound & complex."nOut of 57 studied cases, 31 cases (54.2%) were of complex type; 12 cases (21 %) were compound & 8"ncases were of cystic. The age of incidence ranged from 5.5 to 68 years. The mean age in complex"nodontoma was 27 years & compound type was 19 years. There was no significant difference regarding the"nsex in the complex type. In compound odontoma women were affected 2 times more than means."nComplex type are found in mandibular posterior era ereas more and compound type in anterior regions .In"nthis studied found 12 cases impaction teeth.